2014
DOI: 10.1145/2590772
|View full text |Cite
|
Sign up to set email alerts
|

Nearly Optimal Solutions for the Chow Parameters Problem and Low-Weight Approximation of Halfspaces

Abstract: The Chow parameters of a Boolean function f : {−1, 1} n → {−1, 1} are its n + 1 degree-0 and degree-1 Fourier coefficients. It has been known since 1961 [Chow 1961;Tannenbaum 1961] that the (exact values of the) Chow parameters of any linear threshold function f uniquely specify f within the space of all Boolean functions, but until recently [O'Donnell and Servedio 2011] nothing was known about efficient algorithms for reconstructing f (exactly or approximately) from exact or approximate values of its Chow par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 48 publications
(99 reference statements)
1
58
1
Order By: Relevance
“…So Theorem 7 shows that for a specific natural function, taking k to be constant and letting ε vary, getting an ε-approximator over the Hamming ball {0, 1} n ≤k (for k constant) requires weights that are exponentially larger than the weights required for ε-approximation over the entire Boolean cube. Theorem 7 is also in sharp contrast with the recent upper bound of [2] which shows that there is always an ε-approximator over the entire Boolean cube which has weight at most quasipoly(1/ε) (as a function of ε).…”
Section: Lower Bounds For Approximat-ing Halfspacesmentioning
confidence: 68%
See 2 more Smart Citations
“…So Theorem 7 shows that for a specific natural function, taking k to be constant and letting ε vary, getting an ε-approximator over the Hamming ball {0, 1} n ≤k (for k constant) requires weights that are exponentially larger than the weights required for ε-approximation over the entire Boolean cube. Theorem 7 is also in sharp contrast with the recent upper bound of [2] which shows that there is always an ε-approximator over the entire Boolean cube which has weight at most quasipoly(1/ε) (as a function of ε).…”
Section: Lower Bounds For Approximat-ing Halfspacesmentioning
confidence: 68%
“…(1/ε 2/3 ) by [3], and very recently [2] have further improved the upper bound to √ n · (1/ε) O(log 2 (1/ε)) .…”
Section: Prior Work On Approximation Over {0 1}mentioning
confidence: 99%
See 1 more Smart Citation
“…[Ser07] showed that every n-variable halfspace over {0, 1} n can be ε-approximated by a halfspace of weight √ n · 2Õ (1/ε 2 ) , and showed an Ω( √ n) lower bound for constant ε. The upper bound was subsequently improved (as a function of ε) to weight n 3/2 · 2Õ (1/ε 2/3 ) by [DS09], and very recently [DDFS12] have further improved the upper bound to √ n · (1/ε) O(log 2 (1/ε)) .…”
Section: Previous Work and Our Resultsmentioning
confidence: 99%
“…The high level idea in the proof of Theorem 9 is to exploit the so-called "structure versus randomness" phenomenon for halfspaces which was introduced in the influential work of Servedio [43] and has subsequently played a crucial role in the recent developments in the complexity theoretic analysis of halfspaces [43,18,15,33,32] (we explain this phenomenon a little later). Results in this line of work have mostly looked at halfspaces of the form g(X 1 , .…”
Section: Theoremmentioning
confidence: 99%